Innovation in Traditional Food Processing Technology to Enhance Competitiveness of Local Products in the Global Market - Megavitry, Rissa; Pahrijal, Rival; Novitasari, Salwa Aulia (West Science Agro, 2024)
This study examines the role of innovation in traditional food processing technologies to enhance the competitiveness of local products in the global market. A systematic literature review was conducted on 23 peer-reviewed articles indexed in the Scopus database to identify advancements, challenges, and opportunities in this field. The findings reveal that modern processing innovations, such as preservation techniques, automation, and sustainable practices, significantly improve product quality, scalability, and marketability. However, barriers such as high costs, skill gaps, and regulatory challenges hinder widespread adoption. The study emphasizes the importance of balancing technological innovation with cultural authenticity to ensure long-term sustainability. Recommendations include fostering collaborative efforts among producers, policymakers, and researchers to address adoption barriers and capitalize on emerging global consumer trends. This research contributes valuable insights into the integration of technology in traditional food industries, providing a roadmap for achieving competitiveness while preserving cultural identity.